A systematic review of quality of life in head and neck cancer treated with surgery with or without adjuvant treatment. Issue 10 (October 2015) - Rathod, Shrinivas; Livergant, Jonathan; Klein, Jonathan; Witterick, Ian; Ringash, Jolie
Highlights Systematic review with rigorous quality criteria. Interrogates QoL data in HNC managed with surgery. Limitations in design, reporting, interpretation and knowledge translation were found. Reports symptom burden, temporal trends and predictive factors affecting QoL. Advocates compliance to reporting guidelines to improve usability of QoL data.